THE DYNAMICS OF CONTEMPORARY ISLAMIC CIVILIZATION IN EGYPT (POST-REFORM MOVEMENT ANALYSIS) - Arif Budiono; Farida Huseynova (Universitas Kiai Abdullah Faqih Gresik, 2026)
This study analyzes the dynamics of reform in Egypt in the economic, socio-cultural, religious, and educational fields, and its implications for the formation of contemporary Egyptian society. Using a historical-analytical approach, this study traces the reform process since the early 19th century, triggered by the modernization of the state, interaction with the West, and the response of Muslim intellectuals to the challenges of modernity. The results of the study show that economic reform has transformed the structure of production and social classes, while simultaneously giving rise to inequalities that affect social stability. In the socio-cultural realm, reform drives shifts in values, social relations, and expressions of identity, occurring through a dialectic between tradition and modernity. Meanwhile, religious and educational reform plays a significant role in shaping more rational, reflective, and contextual patterns of religiosity through the reform of Islamic thought and the modernization of educational institutions, including al-Azhar. This study emphasizes that reform in Egypt is not a linear process, but rather a continuous negotiation between religion, state, and society, resulting in a typology of contemporary Egyptian society that is religious, adaptive, and critical in facing global challenges